Análisis del diseño de producción del largometraje ecuatoriano Nice Guy Julio - Zambrano Contreras, Raúl Gustavo (2020)
This type of research has compiled a number of significant investigations, where you can see general concepts and elements of a cinematographic cinema. Fiction cinema or also known as independent cinema are low – budget productions of a small productions of a small productions Company. This type of cinema exposses stories and arguments bet with non - standard cinematographic discourses that address different topics such as: love, death, life, etc., in turn also highlights the personal relationship that exists between the author and the creation, which therefore general has the sea of the director who perfoms it. The general objective of this study is to analyze the cinematographic productions of Nice Guy Julio, this drama genre feature film of 70 – minute, written and directed by the filmmaker Jhonny Obando, developed in Guayaquil, Manabí and Esmeraldas, production house Renacer Films, Distribution FesticGye Foundation, choral cast, of a single location, audiovisual narration poetic style. This production demonstrates the human being in all its fragility (psychology and physics). Within the methodological stucture, it develops an investigation of observation type and in – depth interview.